Method for realizing high-temperature brazing of Cf / SiC composite material and YSZ ceramic based on Ti-Ni-Nb composite intermediate layer

By adopting the vacuum diffusion connection method of TI-Ni-NB composite intermediate layers between YSZ ceramics and CF/SIC composite materials, the problem of insufficient anti-thermal shock resistance in the existing technology under high temperature conditions is solved. Connection effect of intensity and high service temperature.

CN119328250AActive Publication Date: 2025-01-21HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411625392.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-21
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The prior art is difficult to realize high-strength and high service temperature connections between YSZ ceramics and Cf/SiC composites, especially under high temperature conditions, the joints have weak thermal shock resistance and are prone to cracking.

Method used

Using a method based on the Ti-Ni-Nb composite intermediate layer, the TiNiNb composite foil is formed through the pre-welding treatment of YSZ ceramics and Cf/SiC composite materials and the pre-welding treatment of the Ti-Ni-Nb composite foil, and under vacuum conditions Perform vacuum diffusion joining and achieve high temperature brazing.

Benefits of technology

A high-quality metallurgical bonding between YSZ ceramics and Cf/SiC composite materials is achieved. The room temperature shear strength of the joint can reach 59MPa, the shear strength at 500℃ can reach 48MPa, and the shear strength at 1000℃ can reach 11MPa, which is significantly improved. High temperature resistance of joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328250A_ABST
    Figure CN119328250A_ABST
Patent Text Reader

Abstract

The invention discloses a method for achieving high-temperature brazing of a Cf / SiC composite material and YSZ ceramic based on a Ti-Ni-Nb composite middle layer, and relates to the technical field of dissimilar material brazing. The invention aims to solve the problem that a high-strength and high-service-temperature connection joint is difficult to form between the existing YSZ ceramic and the Cf / SiC composite material. According to the method, high-quality metallurgical bonding can be achieved for a Cf / SiC and YSZ ceramic connection joint, under the conditions that the brazing temperature is 1190 DEG C and the heat preservation time is 20 min, the highest room-temperature shear strength of the joint can reach 59 MPa, the highest shear strength at the temperature of 500 DEG C can reach 48 MPa, the shear strength at the temperature of 1000 DEG C can reach 11 MPa, and the high-temperature resistance of the joint is guaranteed while connection of the Cf / SiC and the YSZ ceramic is achieved. According to the method for achieving high-temperature brazing of the Cf / SiC composite material and the YSZ ceramic based on the Ti-Ni-Nb composite middle layer, the high-temperature brazing of the Cf / SiC composite material and the YSZ ceramic can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of brazing of dissimilar materials, and in particular to a method for achieving C f / SiC composite material and YSZ ceramic high temperature brazing method. Background Art

[0002] Modern aircraft engines are developing towards high thrust-to-weight ratio and high maneuverability, especially the new generation of variable cycle engines, and the engine thrust and lift have reached a new height. The tail nozzle is a key component for aircraft engines to generate thrust and lift. The magnitude and direction of the thrust generated have a decisive influence on the performance of aircraft engines. This requires aircraft engines to have high thrust-to-weight ratio and high maneuverability. f The adjustment of the expansion adjusting plate of the / SiC composite tail nozzle is more accurate and rapid, which is achieved through the transmission of the metal ear seat connected to it. f / SiC composite expansion regulating plates are exposed to aerodynamic forces and high-temperature aerodynamic heat (up to 1000°C) for a long time, while the metal ear seat has limited temperature resistance. Therefore, it is necessary to introduce high-temperature resistant insulation materials with low thermal conductivity to control the temperature of the metal ear seat, thereby slowing down the deformation and cracking of the metal ear seat.

[0003] Yttria-stabilized zirconia ceramics (YSZ ceramics for short) are an advanced ceramic thermal insulation material. They are composed of zirconium oxide and stabilizer yttria. They have high melting point, excellent insulation performance, thermal stability and toughness. They are widely used in high-temperature structural materials, heat-resistant materials and other fields. Therefore, YSZ ceramics can be used as C in aircraft engines. f / SiC composite material expansion adjustment sheet and metal ear seat insulation material. The main difficulty in the application of YSZ ceramic insulation layer is how to achieve C f It can ensure reliable connection between the YSZ ceramic insulation layer and the SiC composite material, and ensure that the joint has strong high-temperature service capability.

[0004] YSZ ceramics are currently mainly connected by air reaction brazing or glass brazing sintering. Air reaction brazing mainly uses Ag as the matrix and adds various oxides, but it is difficult to meet the instantaneous high temperature conditions of 1000°C. Glass brazing will produce a certain degree of crystallization during the sintering process, which will deteriorate the mechanical properties of the glass, resulting in weak thermal shock resistance of the joint under this process and easy cracking.

[0005] At present, there are few reports on high-temperature vacuum brazing of YSZ ceramics. Some scholars use TiNi metal brazing filler metal to connect YSZ ceramics to stainless steel. The melting point of the brazing filler metal can reach 942℃, but it still does not reach the service temperature of the aircraft tail nozzle expansion regulator. (Indacochea J E. Polar A. Interface development in joining yttria stabilizedzirconia to stainless steel by in-situ alloying with Ni / Ti filler metals, 2007.) Therefore, a method for high-temperature vacuum brazing of YSZ ceramics and C f High temperature brazing method of SiC composite materials is very important for obtaining C / SiC composite materials with stronger temperature resistance. f / SiC composite material expansion adjustment plate and metal ear seat joint, which is of great significance to increase the tail nozzle outlet temperature and improve the engine thrust-to-weight ratio. Summary of the invention

[0006] The purpose of the present invention is to solve the existing YSZ ceramics and C f The problem that it is difficult to form a high-strength and high-service temperature connection joint between C / SiC composite materials is solved. f / SiC composite material and YSZ ceramic high temperature brazing method.

[0007] A method for realizing C based on Ti-Ni-Nb composite intermediate layer f The method for high temperature brazing of / SiC composite material and YSZ ceramic is carried out in the following steps:

[0008] Step S1: YSZ ceramics and C f Pre-welding treatment of SiC composite materials;

[0009] YSZ ceramic and C f / SiC composite materials are cut, then polished and ultrasonically cleaned to obtain the processed YSZ ceramics and C f / SiC composite materials;

[0010] Step S2: pre-welding treatment of the Ti-Ni-Nb composite foil;

[0011] The Ti, Ni and Nb foils are cut, polished and ultrasonically cleaned, and then the Ti, Ni and Nb foils are bonded together in the order of Ti / Ni / Nb / Ni / Ti under vacuum conditions, and finally pressure is applied to the bonded composite foil to obtain a TiNiNb composite foil;

[0012] Step S3: assembling the test piece to be welded;

[0013] The processed YSZ ceramics obtained in step S1 and C f / SiC composite material and the TiNiNb composite foil obtained in step S2, from bottom to top according to the YSZ ceramic / composite foil / C f / SiC composite materials are stacked in sequence to obtain an assembly;

[0014] Step S4: vacuum diffusion connection;

[0015] Apply pressure to the assembly obtained in step S3, then heat it to 900-1000°C under vacuum, and then continue to heat it to 1160-1190°C, and keep it at 1160-1190°C for 10-60 minutes; after the insulation is completed, cool it to 20-200°C to complete the C based on Ti-Ni-Nb composite intermediate layer. f High temperature brazing of / SiC composite materials and YSZ ceramics.

[0016] Beneficial effects of the present invention:

[0017] (1) The present invention is a method for realizing C based on a Ti-Ni-Nb composite intermediate layer f The method for high temperature brazing of SiC / SiC composite material and YSZ ceramic is based on the fact that Nb element can react with TiNi eutectic phase to form pseudo binary phase at about 1150°C, thereby increasing the service temperature of the joint. At the same time, the introduction of Nb element reduces the Ti-Ni brittle phase, and the (Nb, Ti) solid solution in the pseudo binary eutectic structure has high plasticity, which helps to improve the mechanical properties of the joint. Finally, the present invention forms a high-quality high temperature resistant joint based on the reaction brazing principle.

[0018] (2) The present invention can make C f The joint of SiC and YSZ ceramics is metallurgically bonded to achieve high quality. Under the conditions of brazing temperature of 1190℃ and holding time of 20min, the shear strength of the joint at room temperature can reach up to 59MPa, the shear strength at 500℃ can reach up to 48MPa, and the shear strength at 1000℃ can reach 11MPa (there is no data in the literature that can meet the service temperature of 1000℃). f / SiC and YSZ ceramics are connected while ensuring the high temperature resistance of the joint.

[0019] The present invention can obtain a method for realizing C based on Ti-Ni-Nb composite intermediate layer. f / SiC composite material and YSZ ceramic high temperature brazing method. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1The YSZ ceramic obtained in Example 1 and the C f SEM morphology of the joint of / SiC composite material;

[0021] Figure 2 The YSZ ceramic obtained in Example 2 and the C f SEM morphology of the joint of / SiC composite material;

[0022] Figure 3 A schematic diagram showing the brazing assembly of a base material and a brazing filler metal in the present invention. DETAILED DESCRIPTION

[0023] Specific implementation method 1: This implementation method is based on a Ti-Ni-Nb composite intermediate layer to achieve C f The method for high temperature brazing of / SiC composite material and YSZ ceramic is carried out in the following steps:

[0024] Step S1: YSZ ceramics and C f Pre-welding treatment of SiC composite materials;

[0025] YSZ ceramic and C f / SiC composite materials are cut, then polished and ultrasonically cleaned to obtain the processed YSZ ceramics and C f / SiC composite materials;

[0026] Step S2: pre-welding treatment of the Ti-Ni-Nb composite foil;

[0027] The Ti, Ni and Nb foils are cut, polished and ultrasonically cleaned, and then the Ti, Ni and Nb foils are bonded together in the order of Ti / Ni / Nb / Ni / Ti under vacuum conditions, and finally pressure is applied to the bonded composite foil to obtain a TiNiNb composite foil;

[0028] Step S3: assembling the test piece to be welded;

[0029] The processed YSZ ceramics obtained in step S1 and C f / SiC composite material and the TiNiNb composite foil obtained in step S2, from bottom to top according to the YSZ ceramic / composite foil / C f / SiC composite materials are stacked in sequence to obtain an assembly (such as Figure 3 shown);

[0030] Step S4: vacuum diffusion connection;

[0031] Apply pressure to the assembly obtained in step S3, then heat it to 900-1000°C under vacuum, and then continue to heat it to 1160-1190°C, and keep it at 1160-1190°C for 10-60 minutes; after the insulation is completed, cool it to 20-200°C to complete the C based on Ti-Ni-Nb composite intermediate layer. f High temperature brazing of / SiC composite materials and YSZ ceramics.

[0032] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that in step S1, YSZ ceramics and C f The surface to be welded of the SiC composite material was polished in stages using 600-mesh, 1000-mesh and 1500-mesh sandpaper.

[0033] The other steps are the same as those in the first specific implementation.

[0034] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: in step S1, YSZ ceramics and C f The / SiC composite material is placed in ethanol or acetone and ultrasonically cleaned at a frequency of 70 to 150 kHz for 5 to 30 minutes.

[0035] The other steps are the same as those in the first or second embodiment.

[0036] Specific implementation method 4: The difference between this implementation method and specific implementation methods 1 to 3 is that: in step S2, 3000-mesh and 5000-mesh sandpaper are used to grind the upper and lower surfaces of the Ti, Ni and Nb foils step by step.

[0037] The other steps are the same as those in Specific Embodiments 1 to 3.

[0038] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that in step S2, the Ti, Ni and Nb foils are placed in ethanol or acetone and ultrasonically cleaned at a frequency of 70 to 150 kHz for 5 to 30 minutes.

[0039] The other steps are the same as those in Specific Embodiments 1 to 4.

[0040] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that in step S2, the thickness ratio of the Ti foil to the Ni foil is 8:(5-10), and the thickness ratio of the Ni foil to the Nb foil is 6:(4-10).

[0041] The other steps are the same as those in Specific Embodiments 1 to 5.

[0042] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that the pressure applied in step S2 is 5 to 10 MPa.

[0043] The other steps are the same as those in Specific Embodiments 1 to 6.

[0044] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the pressure applied in step S4 is 0.05-0.2 MPa.

[0045] The other steps are the same as those in Specific Embodiments 1 to 7.

[0046] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the vacuum degree in step S4 reaches 5×10 -3 Heating started at Pa.

[0047] The other steps are the same as those in Specific Embodiments 1 to 8.

[0048] Specific embodiment ten: The difference between this embodiment and specific embodiments one to nine is that in step S4, the two heating rates are 8-12°C / min and 3-6°C / min respectively, and the cooling rate is 3-6°C / min.

[0049] The other steps are the same as those in Specific Embodiments 1 to 9.

[0050] The following examples are used to verify the beneficial effects of the present invention:

[0051] Example 1: A method for realizing C based on Ti-Ni-Nb composite intermediate layer f The method for high temperature brazing of / SiC composite material and YSZ ceramic is carried out in the following steps:

[0052] Step S1: YSZ ceramics and C f Pre-welding treatment of SiC composite materials;

[0053] Cut the YSZ ceramic into 16mm×8mm×3mm cubes by diamond cutting. For the 16mm×8mm×3mm cubic YSZ ceramic, any 16mm×8mm surface is used as the welding surface. f / SiC composite materials are cut into 4mm×4mm×3mm by diamond cutting. f / SiC composite material, any 4mm×4mm surface thereof is used as the surface to be welded;

[0054] YSZ ceramic and C f The surface to be welded of the YSZ / SiC composite material was polished step by step with 600-mesh, 1000-mesh and 1500-mesh sandpaper to remove surface impurities and ensure that the surface to be welded was smooth and flat; after polishing, it was placed in ethanol and ultrasonically cleaned in an ultrasonic cleaning machine at a frequency of 100kHz for 5 minutes. During the cleaning process, ethanol or acetone was replaced and the cleaning was repeated twice. The cleaned YSZ ceramics and Cf The / SiC composite material is placed in a vacuum bag for later use;

[0055] Step S2: pre-welding treatment of the Ti-Ni-Nb composite foil;

[0056] Cut the Ti, Ni and Nb foils with scissors to obtain 7 mm × 7 mm Ti, Ni and Nb foils, then use 3000 mesh and 5000 mesh sandpaper to polish the upper and lower surfaces of the Ti, Ni and Nb foils step by step, put them in ethanol after polishing, and ultrasonically clean them in an ultrasonic cleaner at a frequency of 100 kHz for 5 minutes, and then put the cleaned foils into vacuum bags separately; use a spot welder to bond the Ti, Ni and Nb foils together in the order of Ti / Ni / Nb / Ni / Ti, and then use two flat surfaces to hold the foils and apply a pressure of 5 MPa to obtain a TiNiNb composite foil, which is flattened and sealed for later use;

[0057] The thickness ratio of Ti foil to Ni foil is 8:5, and the thickness ratio of Ni foil to Nb foil is 6:5;

[0058] Step S3: assembling the test piece to be welded;

[0059] YSZ ceramics, TiNiNb composite foil and C f / SiC composite material from bottom to top according to 16mm×8mm×3mmYSZ ceramic (to be welded facing up) / TiNiNb composite foil / 4mm×4mm×3mm C f / SiC composite materials (with the surface to be welded facing downward) are stacked in sequence to obtain an assembly;

[0060] Step S4: vacuum diffusion connection;

[0061] The assembled parts were placed in the furnace, and a pressure of 0.1 MPa was applied along the axial direction of the welded surface by the pressure head to ensure close contact between the base material and the TiNiNb composite foil; then the vacuum was drawn to 5×10 -3 Heating was started at 0.05°C / min, first heated to 1000°C at a rate of 10°C / min, then continued to heat to 1180°C at a rate of 5°C / min, and kept at 1180°C for 20 minutes; after the insulation, it was cooled to 200°C at a rate of 5°C / min, the specimen was taken out, and a connection joint was obtained.

[0062] The shear test was carried out using an electronic universal testing machine with a loading speed of 0.5 mm / min. In this embodiment, the composite foil was used as the solder to connect the YSZ ceramic and C f / SiC composite material, the resulting connection joint has a room temperature shear strength of 33MPa and a shear strength of 30MPa at 500°C.

[0063] Embodiment 2: A method for realizing C based on Ti-Ni-Nb composite intermediate layer f The method for high temperature brazing of / SiC composite material and YSZ ceramic is carried out in the following steps:

[0064] Step S1: YSZ ceramics and C f Pre-welding treatment of SiC composite materials;

[0065] Cut the YSZ ceramic into 16mm×8mm×3mm cubes by diamond cutting. For the 16mm×8mm×3mm cubic YSZ ceramic, any 16mm×8mm surface is used as the welding surface. f / SiC composite materials are cut into 4mm×4mm×3mm by diamond cutting. f / SiC composite material, any 4mm×4mm surface thereof is used as the surface to be welded;

[0066] YSZ ceramic and C f The surface to be welded of the YSZ / SiC composite material was polished step by step with 600-mesh, 1000-mesh and 1500-mesh sandpaper to remove surface impurities and ensure that the surface to be welded was smooth and flat; after polishing, it was placed in ethanol and ultrasonically cleaned in an ultrasonic cleaning machine at a frequency of 100kHz for 5 minutes. During the cleaning process, ethanol or acetone was replaced and the cleaning was repeated twice. The cleaned YSZ ceramics and C f The / SiC composite material is placed in a vacuum bag for later use;

[0067] Step S2: pre-welding treatment of the Ti-Ni-Nb composite foil;

[0068] Cut the Ti, Ni and Nb foils with scissors to obtain 7 mm × 7 mm Ti, Ni and Nb foils, then use 3000 mesh and 5000 mesh sandpaper to polish the upper and lower surfaces of the Ti, Ni and Nb foils step by step, put them in ethanol after polishing, and ultrasonically clean them in an ultrasonic cleaner at a frequency of 100 kHz for 5 minutes, and then put the cleaned foils into vacuum bags separately; use a spot welder to bond the Ti, Ni and Nb foils together in the order of Ti / Ni / Nb / Ni / Ti, and then use two flat surfaces to hold the foils and apply a pressure of 5 MPa to obtain a TiNiNb composite foil, which is flattened and sealed for later use;

[0069] The thickness ratio of Ti foil to Ni foil is 8:5, and the thickness ratio of Ni foil to Nb foil is 6:5;

[0070] Step S3: assembling the test piece to be welded;

[0071] YSZ ceramics, TiNiNb composite foil and C f / SiC composite material from bottom to top according to 16mm×8mm×3mmYSZ ceramic (to be welded facing up) / TiNiNb composite foil / 4mm×4mm×3mm C f / SiC composite materials (with the surface to be welded facing downward) are stacked in sequence to obtain an assembly;

[0072] Step S4: vacuum diffusion connection;

[0073] The assembled parts were placed in the furnace, and a pressure of 0.1 MPa was applied along the axial direction of the welded surface by the pressure head to ensure close contact between the base material and the TiNiNb composite foil; then the vacuum was drawn to 5×10 -3 Heating was started at 0.05°C / min, first heated to 1000°C at a rate of 10°C / min, then continued to heat to 1190°C at a rate of 5°C / min, and kept at 1190°C for 20 minutes; after the insulation, it was cooled to 200°C at a rate of 5°C / min, the specimen was taken out, and a connection joint was obtained.

[0074] The shear test was carried out using an electronic universal testing machine with a loading speed of 0.5 mm / min. In this embodiment, the composite foil was used as the solder to connect the YSZ ceramic and C f / SiC composite material, the resulting connection joint has a shear strength of 46MPa at room temperature, 42MPa at 500℃, and 11MPa at 1000℃.

[0075] In the high-temperature brazing of YSZ ceramics, the weld formed by BNi4+Ti metal brazing filler metal (Induction brazing for gassealing of anode-supported tubular solid oxide fuel cells using the nickelbased brazing alloy modified by TiH2, 2011) has large cracks on the YSZ ceramic side, and its joint strength is less than 20MPa. In the present invention, the Nb element is added to the TiNi metal brazing filler metal, which not only improves the brittleness of the TiNi brazing filler metal, but also significantly improves the high-temperature resistance of the joint.

[0076] The C used in Examples 1 and 2 f / SiC composite material is a three-dimensional four-directional continuous carbon fiber reinforced silicon carbide ceramic matrix composite material. The material is prepared by the precursor infusion pyrolysis (PIP) method. The density of the material is about 1.54-1.96g / cm 3 The SiC ceramic matrix in the composite material is mainly β-SiC, and the theoretical porosity is 16%.

[0077] Figure 1The YSZ ceramic obtained in Example 1 and the C f SEM morphology of the joint of / SiC composite material, Figure 2 The YSZ ceramic obtained in Example 2 and the C f / SiC composite material connection joint SEM morphology.

[0078] like Figure 1 As shown in the figure, within the brazing temperature range of 1180-1190°C, when the brazing parameters are temperature 1180°C and holding time 20 min, the solid solution and eutectic phase are evenly distributed, and the Nb intermediate layer is not completely dissolved; Figure 2 As shown in the figure, when the temperature is further increased to 1190℃, it can be found that the Nb intermediate layer is completely dissolved, the microstructure is evenly distributed, the parent material side reacts fully, and the strength is significantly improved. This proves that the moderate increase in brazing temperature can improve the solubility of the Nb intermediate layer and finally the YSZ ceramic and C f / SiC composite material connection joints have been significantly improved.

Claims

1. A method for realizing C based on Ti-Ni-Nb composite intermediate layer f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that The method proceeds as follows: Step S1: YSZ ceramics and C f Pre-welding treatment of SiC composite materials; YSZ ceramic and C f / SiC composite materials are cut, then polished and ultrasonically cleaned to obtain the processed YSZ ceramics and C f / SiC composite materials; Step S2: pre-welding treatment of the Ti-Ni-Nb composite foil; The Ti, Ni and Nb foils are cut, polished and ultrasonically cleaned, and then the Ti, Ni and Nb foils are bonded together in the order of Ti / Ni / Nb / Ni / Ti under vacuum conditions, and finally pressure is applied to the bonded composite foil to obtain a TiNiNb composite foil; Step S3: assembling the test piece to be welded; The processed YSZ ceramics obtained in step S1 and C f / SiC composite material and the TiNiNb composite foil obtained in step S2, from bottom to top according to the YSZ ceramic / composite foil / C f / SiC composite materials are stacked in sequence to obtain an assembly; Step S4: vacuum diffusion connection; Apply pressure to the assembly obtained in step S3, then heat it to 900-1000°C under vacuum, and then continue to heat it to 1160-1190°C, and keep it at 1160-1190°C for 10-60 minutes; after the insulation is completed, cool it to 20-200°C to complete the C based on Ti-Ni-Nb composite intermediate layer. f High temperature brazing of / SiC composite materials and YSZ ceramics.

2. A method for realizing C based on Ti-Ni-Nb composite intermediate layer according to claim 1 f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that In step S1, YSZ ceramic and C f The surface to be welded of the SiC composite material was polished in stages using 600-mesh, 1000-mesh and 1500-mesh sandpaper.

3. The method according to claim 1 to realize C based on Ti-Ni-Nb composite intermediate layer f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that In step S1, YSZ ceramic and C f The / SiC composite material is placed in ethanol or acetone and ultrasonically cleaned at a frequency of 70 to 150 kHz for 5 to 30 minutes.

4. The method according to claim 1 to realize C based on Ti-Ni-Nb composite intermediate layer f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that In step S2, 3000-grit and 5000-grit sandpapers are used to grind the upper and lower surfaces of the Ti, Ni and Nb foils step by step.

5. The method according to claim 1 to realize C based on Ti-Ni-Nb composite intermediate layer f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that In step S2, the Ti, Ni and Nb foils are placed in ethanol or acetone and ultrasonically cleaned at a frequency of 70 to 150 kHz for 5 to 30 minutes.

6. A method for realizing C based on a Ti-Ni-Nb composite intermediate layer according to claim 1, 4 or 5. f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that In step S2, the thickness ratio of the Ti foil to the Ni foil is 8:(5-10), and the thickness ratio of the Ni foil to the Nb foil is 6:(4-10).

7. The method according to claim 1 for realizing C based on Ti-Ni-Nb composite intermediate layer f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that The pressure applied in step S2 is 5 to 10 MPa.

8. The method according to claim 1 to realize C based on Ti-Ni-Nb composite intermediate layer f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that The pressure applied in step S4 is 0.05 to 0.2 MPa.

9. The method according to claim 1 for realizing C based on Ti-Ni-Nb composite intermediate layer f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that In step S4, the vacuum degree reaches 5×10 -3 Heating started at Pa.

10. The method according to claim 1 to realize C based on Ti-Ni-Nb composite intermediate layer f A method for high temperature brazing of SiC composite material and YSZ ceramic, characterized in that In step S4, the heating rates are 8-12°C / min and 3-6°C / min respectively, and the cooling rate is 3-6°C / min.

Citation Information

Patent Citations

  • Composite foil brazing material

    CA2007382A1

  • Composite interlayer and method for brazing metal with ceramic and ceramic matrix composite material by utilizing same

    CN104690385A

  • Preparation and soldering methods for Ni-based solder used for soldering Nb-Ti high-temperature alloy

    CN107160059A

  • YSZ ceramic and stainless steel air reaction brazing connection method

    CN110253100A

  • Method for brazed connection of Y2O3-MgO nano-composite ceramic and titanium alloy

    CN118492542A